Potholes and possibilities: a mom’s rough road to success - Jones, Novilette (Young Scholars Grinchenko – Seton International Journal, 2025)
The decision to go back to a place that I previously visited umpteen years ago. Now in my late thirties, I made a choice that many others might believe to be unrealistic, if not impossible. I made this choice because I was determined to pursue my deepest desires. I decided to put myself through college full-time while concurrently being the mother of three children, each possessing a personality distinct from the others. I must attend lectures and make meals, read late into the night, and drop off my children at school; my days are filled with chaos.